Enantiomer‐Specific In Vitro Biotransformation of Select Pharmaceuticals in Rainbow Trout (Oncorhynchus mykiss). Issue 11 (29th July 2013) - Connors, Kristin A.; Du, Bowen; Fitzsimmons, Patrick N.; Chambliss, C. Kevin; Nichols, John W.; Brooks, Bryan W.
ABSTRACT The occurrence of pharmaceuticals in the environment represents a challenge of emerging concern. Many pharmaceuticals are chiral compounds; however, few studies have examined the relative toxicity of pharmaceutical enantiomers to wildlife. Further, our understanding of stereospecific pharmacokinetics remains largely informed by research on humans and a few well‐studied laboratory test animals, and not by studies conducted with environmentally relevant species, including fish. The objective of this study was to investigate whether rainbow trout display stereospecific in vitro metabolism of three common chiral pharmaceuticals. Metabolism by trout liver S9 fractions was evaluated using a substrate depletion approach, which provides an estimate of intrinsic hepatic clearance (CLIN VITRO, INT). No biotransformation was observed for rac‐, R‐, or S‐fluoxetine. Ibuprofen, including both enantiomers and the racemic mixture, appeared to undergo slow metabolism, but the resulting substrate depletion curves did not differ significantly from those of inactive controls. Contrary to relative clearance rates in humans, S(−)‐propranolol was more rapidly cleared than the R(+)‐ enantiomer. This work demonstrates that relative clearance rates and the effects of racemic mixtures in trout could not have been predicted based on human data. Additional research describing species differences and exploring tools for species extrapolation in biomedical and environmental studies is needed. Chirality 25:763–767, 2013, © 2013 Wiley Periodicals, Inc.